Reason, emotion and action a phenomenological analysis - Lat, Marlon Reyes (2014)
Reason and emotions are both human abilities that greatly influence human actions. Most philosophers support the view that reason is superior to emotions inasmuch as most philosophical and scientific problems can only be resolved through rational investigation and intellectual argumentation. There are those few, however, who recognize the role of emotion in the analysis on the role of emotions in making moral decisions as well as in the analysis of human actions. The analysis includes brief descriptions of reason, emotions and action partly from psychological and sociological points of view, while relying heavily on the philosophical and ethical points of view. More specifically, this article discusses certain types of emotions - compassion, sympathy, love fear and anxiety, anger, and jealousy and envy - as well as their implications to human actions.
Keywords: Emotions (Psychology)